Emissão de CO2 do solo associada à calagem em área de conversão de laranja para cana-de-açúcar - Silva, Eliton de F. [UNESP]; Moitinho, Mara R. [UNESP]; Teixeira, Daniel de B. [UNESP]; Pereira, Gener T. [UNESP]; La Scala Junior, Newton [UNESP] (Associação Brasileira de Engenharia Agrícola, 2014)
The soil CO2 emission (FCO2) in agricultural areas is resulting from the interaction of several factors, as amended by the practice of soil management practices and crop, in addition to the local edaphoclimatic conditions. In this study, we aimed to quantify FCO2 influenced by liming and application position (row and interrow old) of the orange crop in conversion area for cultivation of sugar cane in the municipality of Frutal-MG. The treatments evaluated were: Row/CC (row with lime application), Interrow/CC (interrow with application of lime), Row/SC (row without liming) and Interrow/SC (interrow without liming). FCO2, temperature (Ts) and soil moisture (Us) were evaluated over 12 days. The highest average value of FCO2 over the study period was observed in the treatment Row/CC (9.63 µmol m-2 s-1) and the lowest in Interrow/CC (5.92 µmol m-2 s-1) according to the Tukey test. The FCO2 was negatively correlated with Us in Row/CC (r = - 0.56, p < 0.05) and in Row/SC (r = - 0.66, p < 0.05). It was also observed a significant and positive correlation between FCO2 and Ts in Row/CC (r = 0.76, p < 0.001), Row/SC (r = 0.89, p < 0.001) and in Interrow/SC (r = 0.66, p < 0.05). It was observed that liming and position of application (row and interrow) influenced the soil CO2 emissions.

A emissão de CO2 do solo (FCO2) em áreas agrícolas é resultante da interação de diversos fatores, sendo alterada pela prática de manejos do solo e da cultura, além das condições edafoclimáticas locais. Neste estudo, objetivou-se quantificar a FCO2 em função da calagem e posição da aplicação (antiga linha e entrelinha) da cultura da laranja em área de conversão para a cultura da cana-de-açúcar, no município de Frutal-MG. Os tratamentos avaliados foram: Linha/CC (linha com aplicação de calcário); Entrelinha/CC (entrelinha com aplicação de calcário); Linha/SC (linha sem aplicação de calcário), e Entrelinha/SC (entrelinha sem aplicação de calcário). FCO2, temperatura do solo (Ts) e umidade do solo (Us) foram avaliadas durante 12 dias. O maior valor médio da FCO2 ao longo do período de estudo foi observado no tratamento Linha/CC (9,63 µmol m-2 s-1); e o menor, no tratamento Entrelinha/CC (5,92 µmol m-2 s-1), segundo teste de Tukey. A FCO2 foi negativamente correlacionada à Us na Linha/CC (r = - 0,56; p < 0,05) e na Linha/SC (r = - 0,66; p < 0,05). Entre a FCO2 e a Ts, verificou-se correlação positiva e significativa na Linha/CC (r = 0,76; p < 0,001), na Linha/SC (r = 0,89; p < 0,001) e na Entrelinha/SC (r = 0,66; p < 0,05). Observou-se que a calagem e a posição de aplicação (linha e entrelinha) influenciaram nas emissões de CO2 do solo.
Soil CO2 emission associated with liming in area of conversion of orange for sugar cane
Keywords: Calagem; Respiração do solo; Temperatura do solo; Umidade do solo; Liming; Soil respiration; Soil temperature; Soil moisture